Development of LKPD Serial Images to Improve the Imaginative Thinking Ability of Elementary School Students - Indra Daulay, Musnar; Hannum Daulay, Dahraini (Journal of Comprehensive Science, 2025)
This study was motivated by the use of LKPD (Learner Worksheets) which were published in bulk and emphasized more on the material than the questions, so that it did not explore the imagination of students. In addition, the LKPD used has not reflected the cross-disciplinary problem solving approach in accordance with the 2013 Curriculum. This research aims to develop LKPDs with serialized images to increase students' engagement and learning outcomes. The goal is to produce LKPDs that are valid, practical, and effective. The method used is the 4-D development model (define, design, develop, disseminate). The research subjects were fifth grade students of SDN 003 Sorek. The validation of LKPD was done through didactic, construction, and technical aspects. Practicality of LKPD was measured through observation of learning implementation and practicality questionnaire by teachers and students, while effectiveness was assessed from students' learning activities and outcomes. The results showed that the serialized picture-based LKPD was declared valid with an average score of 4.24. Its practicality scored 87.3% in the very practical category, while its effectiveness reached 83.2% in the very effective category. Thus, the developed LKPD is proven to be able to improve students' learning activities and outcomes and support a more interactive and creative learning process. In conclusion, the serial picture-based LKPD for grade V elementary school students has met the criteria of valid, practical, and effective, and makes a positive contribution to the quality of learning.